Avaliação das propriedades mecânicas do concreto com adição de fibras para confecção de anéis pré-moldados segmentados para revestimento de túnel de metrô - Carvalho, André Róseo de (2016)
In Brazil, the applications of Reinforced Concrete with Fiber (CRF) are associated to works of great social demand, such as infrastructure works. Although CRF is used in works that require large volumes of concrete, there is no concern with the definition of more precise fiber contents, revealing a lack of assurance of adequate behavior of the design requirements in an economically viable way. However, the study of CRF is necessary because without careful analysis the CRF can cause an increase in the unit cost and hinder the mobility of the larger particles, thus reducing the fluidity of the material. This study investigates the mechanical behavior of reinforced concrete with steel fibers and polypropylene fibers for the construction of segmented subway flooring staves. For this purpose, the concrete should contain steel fibers in an appropriate content that will promote the transfer of tensions through the cracks, to guarantee the capacity to resist after cracking and fibers of polypropylene enough to minimize the risk of plastic cracking, besides protecting against physical damages in the case Occurrence of fires. The experimental program consisted in evaluating the mechanical properties of steel fiber and polypropylene fiber in concrete. Reinforced concretes with different fiber content (25 kg/m³, 35 kg/m³ and 40 kg/m³) and polypropylene fibers (0,5kg/m³, 1,0 kg/m³ and 1,5 kg/m³) to evaluate mechanical parameters of toughness and fire resistance by means of the high temperature exposure method. Statistical analysis (ANOVA) was used to analyze the results, where a gain of up to 12,89% of compressive strength (CRFA40) was obtained as the steel fiber was added, while for the toughness the results Revealed increases of up to 108,9% of the tenacity factor (CRFA40) proposed for the project. While the analysis of the behavior of the concrete in front of elevated temperatures, it was verified that the adoption of polypropylene fibers acted in an efficient way in the fight against spalling, however it caused a marked reduction of the residual resistance, due to the high heating that caused a series of Reactions in the hardened cement paste.